The Archaeological Park at Stabiae: a Regional Interdisciplinary and Sustainable Approach - Howe, Thomas Noble; Gardelli, Paolo (Actual Problems of Theory and History of Art, 2015)
The site of Stabiae is a very unusual archaeological site. It was not just a site of great luxury or great art: it is the best-preserved example of one of the most important seats of political power and architectural art during the formation of the Roman Empire. Unlike Herculaneum or Oplontis, it is possible to excavate entire villas in their totality. First excavated from 1749 to 1782, reburied and forgotten (though excellent plans were published in 1881), later it attracted very little public or scholarly attention before 1998 when the first steps were made to form the Restoring Ancient Stabiae Foundation. It was rediscovered and partly re-excavated from 1950 by a local high school principal, and in the 1960’s excavation passed to the Superintendancy of Pompei, but it was RAS Foundation — a joint structure under the University of Maryland and the American Academy of Rome, and the Soprintendenza Archeologica di Pompei (later Speciale dei Beni Archeologici di Pompei e Napoli, SANP) that proposed the Master Plan of non-invasive suggestive reconstruction of the site for its further conservation, restoration and maintenance as an archaeological park. A true archaeological park requires a concatenation of features which presents the ruin as embedded in coherent spatial and historical environment, which are available at Stabiae. General principles and certain details of the project are presented and explained by the authors.
Keywords: the Naples Bay; the Vesuvian area; Stabiae; ancient Roman elite maritime villas; Restoring Ancient Stabiae (RAS) Foundation; University of Maryland; the American Academy of Rome; Soprintendenza Archeologica di Pompei; Soprintendenza Speciale per i Beni Archeologici; di Napoli e Pompei (SANP); di Pompei; Ercolano e Stabia (SS-PES); Soprintendenza Speciale dei Beni Culturali di Pompei; Ercolano e Stabia (SPES); Master plan; national secured historical area; archaeological park; restoring of Roman architecture; preservation of archaeological sites